PENGARUH FREE CASH FLOW, STRUKTUR ASET, PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG - Anisa Fauzi; Mohammad Taufik Azis; Imam Hadiwibowo (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2022)
This study purpose to examine and analyze the factors that influence debt policy in financial sector companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The sampling method used in this study is the purposive sampling method, namely the sampling method based on certain criteria. Samples that meet the criteria in this study were 68 companies. The analysis used is multiple linear regression analysis to see the effect of the independent variable on the dependent variable either partially or simultaneously. The results of the analysis show that partially Asset Structure has a positive effect on Debt Policy, Profitability has a negative effect on Debt Policy. while Free Cash Flow and Company Growth have no effect on Debt Policy. Meanwhile, simultaneously Free Cash Flow, Asset Structure, Profitability and Company Growth have an effect on Debt Policy. Keywords: Debt Policy, Free Cash Flow, Asset Structure, Profitability, Company Growthp